Bronchiolar adenoma with EGFR exon 19 deletion mutation: a case report and literature review - Zhang, Shaobo; Liu, Xiaohui; Zhang, Xiaoxia; Zhang, Peng; Feng, Haiming; Jiang, Peng (Frontiers in Oncology, 2025)
BackgroundBronchiolar adenoma (BA) is a benign lung tumor characterized by nodular proliferation of bilayered bronchiolar-type epithelium with a continuous basal cell layer. The genetic characteristics of BA are not well understood. However, mutations commonly associated with lung adenocarcinoma, such as BRAF V600E, epidermal growth factor receptor (EGFR) mutations, and ALK rearrangements, have recently been identified in this context.Case reportThis report describes a case of BA in a 43-year-old male who presented with a mixed ground-glass opacity (mGGO) detected during a routine physical examination. The patient had excellent cardiopulmonary function and no other medical conditions. After evaluation, local surgical resection was performed. Intraoperative frozen section pathology initially suggested adenocarcinoma. However, postoperative immunohistochemical examination confirmed the diagnosis of BA. Next-generation sequencing (NGS) further revealed an EGFR exon 19 deletion mutation.ConclusionThe histological morphology of highly differentiated small invasive adenocarcinomas and microinvasive adenocarcinomas closely resembles that of BAs in intraoperative frozen sections. Additionally, gene mutations linked to adenocarcinoma have been identified in BAs. The potential relationship between these two diseases warrants further investigation.